Recognition of sepsis in primary care: a survey among GPs - Loots, Feike J (BJGP Open, 2017)
BACKGROUND: Early recognition and treatment of sepsis are important to reduce morbidity and mortality. Screening tools using vital signs are effective in emergency departments. It is not known how the decision to refer a patient to the hospital with a possible serious infection is made in primary care. AIM: To gain insight into the clinical decision-making process of GPs in patients with possible sepsis infections. DESIGN & SETTING: Survey among a random sample of 800 GPs in the Netherlands. METHOD: Quantitative questionnaire using Likert scales. RESULTS: One hundred and sixty (20.3%) of questionnaires were eligible for analysis. Based on self-reported cases of possible serious infections, the factors most often indicated as important for the decision to refer patients to the hospital were: general appearance (94.1%), gut feeling (92.1%), history (92.0%), and physical examination (89.3%). Temperature (88.7%), heart rate (88.7%), and blood pressure (82.1%), were the most frequently measured vital signs. In general, GPs more likely referred patients in case of: altered mental status (98.7%), systolic blood pressure <100 mmHg (93.7%), unable to stand (89.3%), insufficient effect of previous antibiotic treatment (87.4%), and respiratory rate ≥22/minute (86.1%). CONCLUSION: The GPs' assessment of patients with possible serious infection is a complex process, in which besides checking vital signs, many other aspects of the consultation guide the decision to refer a patient to the hospital. To improve care for patients with sepsis, the diagnostic and prognostic value of assessing the vital signs and symptoms, GPs' gut feeling, and additional diagnostic tests, should be prospectively studied in the primary care setting.